Exploration of Intrinsic Microbial Community Modulators in the Rice Endosphere Indicates a Key Role of Distinct Bacterial Taxa Across Different Cultivars - Wang, Pei; Kong, Xiao; Chen, Hongsong; Xiao, Youlun; Liu, Huijun; Li, Xiaojuan; Zhang, Zhuo; Tan, Xinqiu; Wang, Diandong; Jin, Decai; Deng, Ye; Cernava, Tomislav (Frontiers in Microbiology, 2021)
Microbial communities associated with the plant phyllosphere and endosphere can have both beneficial as well as detrimental effects on their hosts. There is an ongoing debate to which extend the phyllosphere and endosphere microbiome assembly is controlled by the host plant how pronounced cultivar effects are. We investigated the bacterial and fungal communities from the phyllosphere and endosphere of 10 different rice cultivars grown under identical environmental conditions in the frame of a targeted approach to identify drivers of community assembly. The results indicated that the endophytic bacterial communities were clearly separated into two groups. The α-diversity and microbial network complexity within Group I were significantly lower than in group II. Moreover, the genera Nocardioides, Microvirga, and Gaiella were significantly more abundant in Group II and only present in the interaction networks of this group. These three genera were significantly correlated with α- and β-diversity of the endophytic bacterial community and thus identified as major drivers of the endosphere community. We have identified keystone taxa that shape endophytic bacterial communities of different rice cultivars. Our overall findings provide new insights into plant-microbe interactions, and may contribute to targeted improvements of rice varieties in the future.